2022
DOI: 10.1177/20551169221114330
|View full text |Cite
|
Sign up to set email alerts
|

Feline gastrointestinal eosinophilic sclerosing fibroplasia presenting as a rectal mass

Abstract: Case summary A 9-year-old neutered male cat was referred owing to dyschezia and weight loss. Abdominal CT revealed a heterogeneous mass in the rectum and thickening of one caudal mesenteric lymph node. The mass induced a focal rectal obstruction. Cytological evaluation of fine-needle aspirates showed signs of mixed inflammation for the rectal mass and a reactive lymph node. Because a definite diagnosis was not achieved, complete resection of the mass via a dorsal approach to the rectum was attempted. Histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Similarly, research on CT studies of FGESF remains limited, with only two reported cases of FGESF located in the extramural retroperitoneal area and rectum (Lawrance et al 2001;Thieme et al 2019). In these two cases, FGESF showed heterogeneous contrast enhancement on CT, in contrast with our case, which illustrated mild homogeneous contrast enhancement (Thieme et al 2019;Goffart et al 2022). Considering the absence of necrotic lesions on the histological examination in case 1, the contrast enhancement pattern difference is likely attributable to the presence or absence of necrotic lesions.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Similarly, research on CT studies of FGESF remains limited, with only two reported cases of FGESF located in the extramural retroperitoneal area and rectum (Lawrance et al 2001;Thieme et al 2019). In these two cases, FGESF showed heterogeneous contrast enhancement on CT, in contrast with our case, which illustrated mild homogeneous contrast enhancement (Thieme et al 2019;Goffart et al 2022). Considering the absence of necrotic lesions on the histological examination in case 1, the contrast enhancement pattern difference is likely attributable to the presence or absence of necrotic lesions.…”
Section: Discussionmentioning
confidence: 43%
“…Feline gastrointestinal eosinophilic sclerosing fibroplasia (FGESF) is a recently described eosinophilic nodular mass located within the gastrointestinal tract (Craig et al 2009;Linton et al 2015). Although a few studies and case reports have been reported on FGESF, computed tomography (CT) features are limited to the extramural retroperitoneal area and rectum (Thieme et al 2019;Goffart et al 2022). A recent study on FGESF reported ul-trasonographic findings in 30 cats, revealing typical features such as a loss of intestinal layering, thickening, and mixed wall echogenicity with hyperechoic areas, particularly in gastric or intestinal cases (Cerna et al 2024).…”
mentioning
confidence: 99%
“…1,9,12,13 A multimodal approach is currently recommended with a combination of debulking surgery, when possible, together with antimicrobial and immunosuppressive therapy (prednisolone with or without ciclosporine). 1,9,10,[12][13][14] Despite adopting this multimodal approach, in the case reported here, death occurred only 2 months after diagnosis. The cause remained undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because of an earlier diagnosis as a result of increased awareness, as well as improved understanding of the pathogenesis of the condition resulting in more appropriate management. 1,9,12,13 A multimodal approach is currently recommended with a combination of debulking surgery, when possible, together with antimicrobial and immunosuppressive therapy (prednisolone with or without ciclosporine). 1,9,10,[12][13][14] Despite adopting this multimodal approach, in the case reported here, death occurred only 2 months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation